2012
DOI: 10.1007/978-3-642-31680-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Website Detection Using Remote Traffic Analysis

Abstract: Abstract. Recent work in traffic analysis has shown that traffic patterns leaked through side channels can be used to recover important semantic information. For instance, attackers can find out which website, or which page on a website, a user is accessing simply by monitoring the packet size distribution. We show that traffic analysis is even a greater threat to privacy than previously thought by introducing a new attack that can be carried out remotely. In particular, we show that, to perform traffic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…Several related works do not focus on website fingerprinting in particular, but rather on the detection of other distinct characteristics of network traffic, e.g., the language of a Voice-over-IP (VoIP) call [30], or spoken phrases in encrypted VoIP calls [29]. Gong et al [10] even showed the feasibility of a remote traffic analysis (where the adversary does not directly observe the traffic pattern) by exploiting queuing side channel in routers.…”
Section: A Traffic Analysis On Encrypted Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several related works do not focus on website fingerprinting in particular, but rather on the detection of other distinct characteristics of network traffic, e.g., the language of a Voice-over-IP (VoIP) call [30], or spoken phrases in encrypted VoIP calls [29]. Gong et al [10] even showed the feasibility of a remote traffic analysis (where the adversary does not directly observe the traffic pattern) by exploiting queuing side channel in routers.…”
Section: A Traffic Analysis On Encrypted Connectionsmentioning
confidence: 99%
“…We then randomly selected a link with a probability of 0.5 from the first, 0.25 from the second, 0.125 from the third, and 0.0625 from the fourth and fifth result pages and included the selected target web page in our dataset. 4) Googling at random: We selected 20,000 English terms at random from the Beolingus German-English dictionary 10 and entered them into Google Search. From the results, we selected web pages with the same method as described for Google trends.…”
Section: B Rnd-www: An Unbiased Random Sample Of the World Wide Webmentioning
confidence: 99%
“…However, in this section we used our approach with Https traffic and the results are showed in table (6). The results in table 6 shows a good result for Https traffic using 3-gram, unless for google.com this is due to the natural design of google web page that has a less content.…”
Section: Second Level (Https) Websites Fingerprintmentioning
confidence: 96%
“…Gong in [6] proposed work is trying to prove that the remote traffic analysis could be used by eavesdroppers. The adversary can identify the websites that a remote user is accessing by knowing his/her IP address.…”
Section: Related Workmentioning
confidence: 99%
“…Gong et al [26] present a kind of inference attack using RTT measurement to infer which website the victim is browsing. They recover victims' network traffic patterns based on the queuing side channel happened at the Internet router.…”
Section: Related Workmentioning
confidence: 99%